CHANGES IN METABOLIC AND RENAL SYSTEM AFTER HCV CLEARANCE IN CHRONIC VIRAL HEPATITIS PATIENTS TREATED WITH DIRECT-ACTING ANTIVIRALS - PASHA, H; TARIQ, AT; BANGASH, A; SALIM, M; MOHIUDIN, T (Biological and Clinical Sciences Research Journal, 2024)
Chronic hepatitis C infection is associated with metabolic and renal abnormalities, with direct antiviral agents (DAAs) offering a promising treatment approach. However, the influence of hepatitis C virus (HCV) clearance on metabolic and renal parameters in these patients remains underexplored. Objective: This study aimed to assess the impact of HCV clearance on the metabolic and renal system of chronic hepatitis C patients treated with direct antiviral agents. Methods: A prospective study was conducted at the Department of Medicine, Shifa Hospital, Islamabad, from January 2022 to January 2024. A total of 323 patients with chronic hepatitis C treated with DAAs were included. Hepatic and renal function tests were recorded before treatment, post-treatment, and 6-month follow-up. Insulin resistance (IR) and B-cell function were evaluated using the homeostatic model assessment (HOMA). All patients received DAAs treatment, with or without ribavirin. Statistical analysis was performed using appropriate methods. Results: Following HCV clearance, both groups exhibited a significant decrease in fasting glucose and insulin levels and improvements in HOMA-IR values. Additionally, decreased creatinine levels and increased glomerular filtration rate (GFR) indicated enhanced renal function. Sustained virologic response (SVR) emerged as an independent predictor of improvement in GFR and HOMA-IR. Conclusion: HCV clearance in chronic hepatitis C infection, achieved through treatment with direct antiviral agents, leads to notable improvements in renal and metabolic parameters. These findings underscore the importance of achieving SVR in managing chronic hepatitis C.